Prevalence and Patterns of Neonatal Birth Trauma in Ethiopia: Systematic Review and Meta-Analysis - Bikila Balis MSc; Aboma Diriba Hunde MPH; Magarsa Lami MSc (SAGE Publishing, 2023)
Introduction. Neonatal death is still alarming in low-income countries including Ethiopia, accounts 30 death per 1000 alive births. Birth trauma is the second most common contributing factors for the death. Nevertheless, there is no aggregate evidence on the prevalence and patterns of neonatal birth trauma in Ethiopia. Therefore, this study aimed to assess the pooled prevalence and patterns of neonatal birth trauma in Ethiopia. Methods. Searching databases including PubMed, MEDLINE, Popline, SCOPUS, Web of Science, EMBASE, CINHAL (EBSCO), Google, Google Scholar, and lists of references were used to search literatures in Ethiopia. STATA version 14 was used for analysis, and the odds ratios of the outcome variable were determined using the random-effects model. Heterogeneity among the studies was assessed by computing values for I 2 and P -values. Also, sensitivity analysis and funnel plot were done to assess the stability of pooled values to outliers and publication bias. Results. A total of 6 studies with a sample size of 3663 were included in this study. The overall prevalence of neonatal birth trauma was 15% (95% CI: 13-16). Subgaleal hemorrhage (39%), cephalohematoma (27%), and caput succedaneum (24%) were the most common neonatal birth trauma in Ethiopia. Meta-analyses and sensitivity analyses showed the stability of the pooled odds ratios, and the funnel plots did not show publication bias. Conclusion. This systematic review and meta-analysis revealed a high prevalence of neonatal birth trauma in Ethiopia. Moreover, most of the neonatal birth injuries were severe and life-threatening that need medical attention to safe the neonates and its life long complications.